More Up-To-Date Monitoring of Long-Term Survival Rates by Cancer Registries: An Empirical Example - Brenner, H.; Gefeller, O.; Stegmaier, C.; Ziegler, H. (Methods of Information in Medicine, 2001)
A few years ago, a new method of survival analysis, denoted period analysis, has been developed to derive more up-to-date estimates of long-term survival rates of cancer patients, but this method has rarely been applied so far. Using empirical examples from the Saarland Cancer Registry, we illustrate how seriously traditional long-term survival estimates may lag behind survival expectations of newly diagnosed cancer patients in the case of recent improvement in prognosis, and to what extent this problem may be reduced by period analysis of survival. We conclude that period analysis should be more widely used for deriving more up-to-date long-term survival estimates.
Keywords: Cancer Registries; Epidemiological Methods; Survival